Food Supply Chain: Possible Impact and Consequence Analysis of Reducing Working Hours of Food Retailers - Pilvere, Aija; Pilvere, Irina; Proskina, Liga; Cerina, Sallija; Nipers, Aleksejs (Emerging Science Journal, 2025)
Grocery shops constantly follow trends and developments in consumer demand; therefore, solutions are sought to enhance food retailing, and one solution is to limit the working hours of supermarkets to balance the interests of stakeholders and those employed in the food supply chain. Accordingly, the present research aims to identify the possible socio-economic impact of reducing the working hours of food supermarkets in Latvia. The research analyzed primary information sources: publicly available information from databases and annual reports by companies from the industry. Three potential scenarios were designed to identify the socio-economic impact of reducing the working hours of supermarkets. The research found that if the working hours of the four leading food supermarkets (Maxima, Rimi, Lidl, Sky) in Latvia were reduced, their turnover, market shares, and taxes paid to the national government, as well as the hours worked by their employees, would decrease, thereby leading to some redundancies causing some negative socio-economic consequences. The novelty of the research is that retail is an essential link in the food supply chain from farm to fork, making food available to consumers. The calculations show that we should be careful when reducing the working hours of supermarkets because this has socio-economic consequences. It is also necessary to evaluate the attitude of consumers. Doi: 10.28991/ESJ-2025-09-01-05 Full Text: PDF